KDRT DAN KEKERASAN SEKSUAL ( ANALISIS DAN INTERPRETASI DALAM PERSPEKTIF HADITS) - Laudita Soraya Husin, Aisyatin Kamila, Atik Makrifatun Afifah, (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2020)
Talking about domestic life, often the twists and turns of life contribute to strengthening or weakening the family ties that have been built on both sides. Domestic Violence (KDRT) and sexual violence are cases that will weaken and even break family ties into divorce. The majority of the wives or women are victims of domestic violence. Domestic violence and violence can take the form of physical and psychological violence. Domestic violence and sexual violence are certainly against the mission of all forms of religion in the world, particularly in Islam. Islam is a religion that carries a noble mission, namely Rahmatan lil'alamin (the bearer of happiness for all nature. Islamic law which is derived from the Al-Qur'an and the Prophet's Hadiths, aims to maintain and safeguard the benefit of mankind, and uphold human dignity. regardless of gender whether he is male or female. Therefore, Islamic law does not completely justify any form of violence against a person, especially if the violence is confessed only because of the gender of the woman, so that Islam views violence against women as a despicable act. , violates the law and Islamic law. This case can be reviewed and can be analyzed and interpreted the meaning from the perspective of hadith. As legal determination seen from the perspective of hadith.